On the use of the double floating probe method to infer the difference between the electron and the heavy particles temperatures in an atmospheric pressure, vortex-stabilized nitrogen plasma jet - Prevosto, Leandro (2014)
Sweeping double probe measurements in an atmospheric pressure direct current vortex-stabilized plasma jet are reported (plasma conditions: 100 A discharge current, N2 gas flow rate of 25 Nl/min, thoriated tungsten rod-type cathode, copper anode with 5 mm inner diameter). The interpretation of the double probe characteristic was based on a generalization of the standard double floating probe formulae for non-uniform plasmas coupled to a non-equilibrium plasma composition model. Perturbations caused by the current to the probe together with collisional and thermal processes inside the probe perturbed region were taken into account. Radial values of the average electron and heavy particle temperatures as well as the electron density were obtained. The calculation of the temperature values did not require any specific assumption about a temperature relationship between different particle species. An electron temperature of 10 900 ± 900 K, a heavy particle temperature of 9300 ± 900 K, and an electron density of about 3.5 × 1022 m−3 were found at the jet centre at 3.5 mm downstream from the torch exit. Large deviations from kinetic equilibrium were found toward the outer border of the plasma jet. These results showed good agreement with those previously reported by the authors by using a single probe technique. The calculations have shown that this method is particularly useful for studying spraying-type plasma torches operated at power levels of about 15 kW.